1987
DOI: 10.1002/pdi.1960040508
|View full text |Cite
|
Sign up to set email alerts
|

The use of art therapy for diabetics

Abstract: Diabetes may bring with it many emotional problems about which many patients may not be able to easily express their feelings. This has been recognised by physicians and some experiments in the use of psychotherapy have been tried. Art therapy is used in the treatment of mental handicap and mental illness and, as a diabetic, I have successfully used art to help me to cope with my condition. Given appropriate facilities such as a diabetes day centre, art therapy could be offered to patients as another means of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Art therapy has been used in Britain since the 1940s mainly in mentally handicapped, geriatric and oncology units. Unfortunately to date extensive literature research has confirmed that few people have used art therapy in the treatment of diabetes or have evaluated its effectiveness 1…”
Section: Introductionmentioning
confidence: 99%
“…Art therapy has been used in Britain since the 1940s mainly in mentally handicapped, geriatric and oncology units. Unfortunately to date extensive literature research has confirmed that few people have used art therapy in the treatment of diabetes or have evaluated its effectiveness 1…”
Section: Introductionmentioning
confidence: 99%